Framing rhino horn demand reduction in Vietnam: Dismissing medical use as voodoo - Michael Scott Smith (Asia Pacific Network, 2018)
According to Milliken and Shaw (2012) a surge in illegal rhino poaching in South Africa since 2006 was linked to increasing demand for rhino horn in Vietnam. This article examines one of the key frames, the ‘Voodoo Wildlife Parts’ (VWP) frame, which Environmental Non-Government Organisations (ENGOs) in Vietnam have been using in rhino horn demand reduction media campaigns. The VWP frame emerged from the findings of a research project that investigated the news frames present in the media outputs of seven ENGOs, both local and international, opposing the Illegal Wildlife Trade (IWT) in Vietnam.  This article will briefly outline the four frames that emerged from that research, then discuss the two subthemes of the VWP frame and its scientific basis and the nature of the feedback from journalists and the public that influenced the frame’s production.